ANOMALI MONDAY EFFECT PADA BURSA EFEK INDONESIA PERIODE 2000 – 2011 - Marselia Purnama; Janny Rowena (Jurnal Akuntansi Bisnis, 2017)
Days in one week have an effect on behaviour in life. It is very interesting mentioned to be research where there are phenomenon that trading day also have an effect on to rate of return and risk of stock exchange investment. This study examines whether there is an abnormal return came from the Monday effect phenomenon in the Jakarta Stock Exchange, with the sample of daily Jakarta Stock Exchange return in the year of 2000 until 2011. The purpose of these research was to know the empirical impact of days of the Monday  effect to daily stock return. Analysis and data processing perform by SPSS 17.0. The analyse using multiple regression either simultaneously or partial. After the process of analysis and data processing done using statistical method, it can be conclued that the days of trading have significant influence on stock returns in the periode of its study, it may be said that the Monday effect occurs in the Indonesia Stock Exchange during the periode of this study.Key Words :  Anomaly, Monday Effect, Day Trading, Return